2012
DOI: 10.5511/plantbiotechnology.12.0726b
|View full text |Cite
|
Sign up to set email alerts
|

Production of transgenic rice plants expressing Dioscorea batatas tuber lectin 1 to confer resistance against brown planthopper

Abstract: Dioscorea batatas tuber lectin 1 (DB1) is a storage protein isolated from yam tuber and has been shown to be a mannose-binding lectin. Here we produced transgenic rice plants expressing cDNA of DB1 under the control of phloemspecific promoter of rice sucrose synthase-1 gene. DB1 accumulated at a level of 0.07% of total soluble protein. We then evaluated its efficacy for brown planthopper (BPH). After releasing the first instar of BPH on the transgenic rice plants, the number of survived BPH adults was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The second expansion (red band) consisted of 28 mannose-binding lectins sharing high similarity with Dioscorea batatas tuber lectin DB1 (accession number AB178475). DB1 has insecticidal properties against cotton bollworm ( Helicoverpa armigera ), and studies in transgenic tobacco and rice plants expressing DB1 demonstrated that it also confers resistance against green peach aphid and brown plant hopper, respectively [ 22 24 ]. Of these mannose-binding lectin genes in Guinea yam, 16 did not have orthologs in any of the six other species examined, and two showed enriched expression (Benjamini–Hochberg [ 25 ] adjusted P value [padj] < 0.05) in tubers.…”
Section: Resultsmentioning
confidence: 99%
“…The second expansion (red band) consisted of 28 mannose-binding lectins sharing high similarity with Dioscorea batatas tuber lectin DB1 (accession number AB178475). DB1 has insecticidal properties against cotton bollworm ( Helicoverpa armigera ), and studies in transgenic tobacco and rice plants expressing DB1 demonstrated that it also confers resistance against green peach aphid and brown plant hopper, respectively [ 22 24 ]. Of these mannose-binding lectin genes in Guinea yam, 16 did not have orthologs in any of the six other species examined, and two showed enriched expression (Benjamini–Hochberg [ 25 ] adjusted P value [padj] < 0.05) in tubers.…”
Section: Resultsmentioning
confidence: 99%
“…Another major protein stored in Chinese yam tubers is a galactose-binding lectin. This is a defense protein that targets insect pests, suggesting it may be transferrable to other crops (Gaidamashvili et al 2004 ; Ohizumi et al 2009 ; Yoshimura et al 2012 ). This protein has also been shown to inhibit cancer cell growth, and may therefore be useful as a lead to develop new cancer drugs (Yang et al 2011 ; Chan and Ng 2013 ).…”
Section: Chinese Yam Ingredients With Health Benefits and Other Usefumentioning
confidence: 99%
“…It was also reported that transgenic crops expressing garlic lectins (ASA and ASAL) could confer resistance against various lepidopteran and homopteran insects, viz., Nilaparvata lugens , Nephotettix virescens , Sogatella furcifera, Spodoptera littoralis , Lipaphis erysimi and Aphis craccivora [8], [17], [29]-[31]. Further, it was reported that the expression of Dioscorea batatas tuber lectin in rice and tobacco reduced the survival of BPH and aphid by 30% and 60%, respectively [32], [33]. Garlic lectins serve as promising candidate molecules for the development of transgenic crops against sucking pests as they are from edible source, and as such may not pose any biosafety problem.…”
Section: Discussionmentioning
confidence: 99%